Reduction of Chrom Ion (Cr) With Ion Exchange Resin in Liquid Waste of Leather Tanning - Saputri, Resy Mareta Dwi; Aurellia, Pingky Marcella; Perwitasari, Dyah Suci (Nusantara Science and Technology Proceedings)
The leather tanning industry was classified as industrial in large quantities and dangerous. One of the wastes that produced was waste liquid containing chromium ions. The liquid waste that was released was very cloudy, colored, and has rotten management that caused serious problems to water bodies, communities and the environment. The waste without special handling was discharged into the environment. So that with the ion exchange method, it could reduce environmental pollution caused by industrial leather tanning waste. This study aimed to determine the effect of resin in reducing the chromium ion content in the liquid waste of the leather tanning industry using the ion exchange method. Namely, by consolidating waste and resin with various predetermined variables. The positively charged chromium ion will exchange with the H+ ion found in dowex resin. So that the chromium levels in the tannery liquid waste could be reduced. The results were obtained by the contact time and weight of the resin used. The highest reduction in chromium ion content was at contact time for 80 minutes with a resin weight of 150 grams of 98.75%.